Materials science and modern manufacturing : selected peer-reviewed full text papers from the 3rd International Scientific Conference of Alkafeel University (ISCKU 2021) : selected peer-reviewed papers from the 3rd International Scientific Conference of Alkafeel University (ISCKU 2021), March 22-23, 2021, Al-Najaf Al-Ashraf, Iraq - Al-Dahan, N.; Alosfur, Firas; Sopian, K. (Trans Tech Publications, Limited, 2021)
Selected peer-reviewed full text papers from the 3rd International Scientific Conference of Alkafeel University (ISCKU 2021) Selected, peer-reviewed papers from the 3rd International Scientific Conference of Alkafeel University (ISCKU 2021), March 22-23, 2021, Al-Najaf Al-Ashraf, Iraq.
Description based upon print version of record.
Studying the Physical Properties of Bi-2223 Nanostructure Prepared Thermal Treatment Method.
Keywords: Manufacturing processes -- Congresses.; Materials science -- Congresses.; Manufacturing industries -- Congresses.; elektronické knihy; electronic books